Theoretical approach to the evaluation of the load-carrying capacity of the tie rod anchor system in a masonry wall. (1st October 2016) - Pisani, Marco Andrea
Highlights: Load-carrying capacity of tie rod anchor plates acting on masonry walls. Theoretical research. Strength is the minimum between the force that starts slippage and the force that starts the extraction of a truncated cone. Design of the minimum thickness of the anchor plate. Examples to show the capabilities of the suggested approach. Abstract: The behaviour of tie rod anchor plates is at present not well established, and the criteria suggested do not seem to have consistent theoretical basis. This paper suggests a theoretical approach to determine the load-carrying capacity of stiff anchor plates acting on a masonry wall. According to this approach the punching strength is the lower of two values. The first value follows from the hypothesis that collapse occurs because of the slippage of the units on the mortar bed, whereas the second comes from the alternative hypothesis that punching creates a solid consisting of a truncated cone in which the outer face is the surface of the anchor plate (units break whereas the mortar does not crumble). When doing so it is supposed that the anchor plate is so stiff that pressure it applies on the masonry wall is almost constant. The issue of setting an adequate stiffness is solved for the most common types of anchor plate. Some numerical examples show the capabilities of the suggested approach.